Reasonable Values and the Value of Reasonableness. Reflections on John Rawls’ Political Liberalism - Roberta Sala (Rosenberg & Sellier, 2016)
This paper aims to question the idea of reasonableness in Rawls’ account of political liberalism. My point is that reasonableness as the moral basis of the liberal society provides restrictions for differences – be they philosophical, moral, religious, cultural – to be included in the liberal society. Notwithstanding Rawls’ attempt to expand political boundaries and to include those people who do not share moral liberal justification to justice as fairness, reasonableness selects “values holders” and assigns to the so-called “reasonable” a place in the political debate. The others, the “unreasonable”, are expected to become reasonable; alternatively, they would be paid control or even coercion in all the circumstances in which they should represent a risk for political stability. I believe that Rawls gives an incomplete account of unreasonableness: there may well be persons who are not “reasonable” in Rawlsian terms but who do not necessarily represent a danger for the just society. By the fact that they do not endorse values as freedom and equality in which fair cooperation is grounded, we cannot infer that they will necessarily try to violate the terms around which cooperation is structured by imposing their values on others. I proceed as follows: a) I detail the Rawlsian political turn in defending justice as fairness; b) I focus on the idea of reasonableness as the core of political liberalism; c) I defend the thesis that political liberalism needs to revise the idea of unreasonableness if it aims to deal with pluralism as a social and political fact.